Inglês para crianças é para inglês ver? : políticas linguísticas, formação docente e educação linguística nas séries iniciais do ensino fundamental no Espírito Santo - Merlo, Marianna Cardoso Reis (2018)
English education to children has been an important area of inquiry, especially for Applied Linguistics. On this matter, many researchers have been investigating how children learn a foreign language as well as teacher childhood education. Some of these studies have acknowledged the existence of a gap between teacher education in undergraduate levels in Brazil and the growing trend of teaching a foreign language to young learners, especially English language education. This study aims at contributing to this debate by carrying out a research about the ways teacher education proposed by two undergrad courses of Letters in Espírito Santo, Brazil, focuses on primary levels. This investigation was based on the analysis of the documents which regulate those courses. Also, from a critical perspective, this research focuses on educators from public schools in order to investigate the relations among educational documents which focus on foreign language education in primary levels in Brazil, the participants’ teacher education, their pedagogical practices and their perspectives about English language education to young learners in public schools. The guiding principles of this research are the post-structuralist philosophies of language. The methodology is qualitative and the method is ethnographic. Findings suggest that it is urgent to bring about that discussion within undergraduate levels in order to contribute to a more consistent and relevant English education for young learners, which is the main purpose of this research.